Discretionary Nihilism as Illegitimate Legitimacy: on the Limits of Normativity in Public Administration - D. I. Zaitsev (Courier of Kutafin Moscow State Law University (MSAL)), 2026)
This article analyzes a category that is new to Russian legal scholarship — discretionary nihilism — which is defined as a distortion of the legal consciousness of the law enforcer, manifested in a negative attitude toward administrative discretion and a refusal to exercise one’s discretionary powers. The author examines discretionary nihilism from an ontological perspective, constructing a specific taxonomy — that is, the relationship between discretionary nihilism and various concepts, in particular «legality», «normativity», and «public administration». To this end, the author first highlights certain differences between discretionary nihilism and legal nihilism, demonstrating the correlation and interdependence between them. The author then discusses legitimate and illegitimate legality, arguing that discretionary nihilism is closely linked to the latter. In the final part of the study, the focus shifts to the conﬂict between the ought (normative-legal) and the is (normative-factual); it is shown that the triumph of the ought gives rise to discretionary nihilism. In conclusion, the author invites representatives of the academic community to join the discussion on discretionary nihilism.